Processos de criação artística comunitária: questões metodológicas - Serafino, Irene (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
From the field experience in a four-year empiric research, integrated in my Ph.D in Sociology, are shown considerations about the role social researchers plays. Thoughts about the Pele_Espaço de Contacto Social e Cultural association’s case study, acts in the city of Porto since 2007, raised questions related to the sociologist interaction with the analyzed context: the “doing" and "being" of the sociologist in the field; the ethical implications; the centrality of in-depth and long-term fieldwork; the balance between, collaboration, approximation, and critical analytical detachment.